1978
DOI: 10.1007/bf01871376
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin variants in Korea and Japan

Abstract: SummarySeveral transferrin variants detected in surveys of serum samples from Koreans and Japanese have been compared critically with standards and with each other using thin layer agarose gel electrophoresis and polyacrylamide gel electrophoresis.All slow-moving variants were found to have identical mobility with a reference sample of CDc~l. Four different fast-moving variants were detected, Bxoro~ 1, B• .... 2, Bj~p. 1 and Bj~p. 3. Their relative mobilities at pH 8.9 and 6.5 have been listed and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In Japanese populations, Parker and Bearn (1961), Matsumoto (1964), Omoto and Harada (1972), and Kirk et al (1978) have reported rare electrophoretic variants. Ferrell et al (1977), examining 4,029 Japanese residing in Hiroshima and Nagasaki, reported three types of B-variant and five types of D-variant.…”
Section: Introductionmentioning
confidence: 98%
“…In Japanese populations, Parker and Bearn (1961), Matsumoto (1964), Omoto and Harada (1972), and Kirk et al (1978) have reported rare electrophoretic variants. Ferrell et al (1977), examining 4,029 Japanese residing in Hiroshima and Nagasaki, reported three types of B-variant and five types of D-variant.…”
Section: Introductionmentioning
confidence: 98%
“…Separation of the genetic variants of the human serum transferrin using electrophoresis in starch gel (Smithies, 1957), agarose gel (Teisberg, 1970) and polyacrylamide gel (Kirk et al, 1978) have shown a common transferrin type, termed transferrin C. It has a frequency of about 98~ or more in all populations so far investigated. Several transferrin variants have also been reported: B variants which have faster and D variants which have slower electrophoretic mobility than transferrin C (Giblett, 1969).…”
Section: Introductionmentioning
confidence: 99%